SUNDAY SCHOOL CHILDREN AND THE IMPONDERABLES OF CHRISTIAN ETHICS: PHILOSOPHICAL REFLECTIONS OF IMMANUEL KANT - Nia Desiska; Oktalia, Linda Lestari Kueain, Tri Sugianto, Melin, Evi Mariani (Adisam Publisher, 2023)
The purpose of this paper is to describe the development and experience of Sunday School teachers in terms of teaching. The authors analyze and describe from the perspective of Immanuel Kant. The opinion put forward by Kant is that morality comes from humans, there is an urge to be obligatory in an action. The research method used is phenomenological quantitative research method and analysis of journals. Kant's rational criticism has great potential in the teaching experience of Sunday school teachers, because basically Kant wants to provide God's workers with an understanding to understand the teachings of a religion with their own morals and logic, in order for the experience gained to have an impact on the surrounding environment and bring good changes to everyone.